Six songs, vols 618, 619 - BEETHOVEN, Ludwig Van (G. Schirmer. Inc., 1902)
Adelaide, Op. 46nMignon, Op. 75, No. 1nIn Questa tomba oscura (in this sepulchral darkness)nMit einem gemalten bande, op. 83, No. 3nFreudvoll und leidvoll, Op. 84, No. 4 (Joyful and woeful)nNeue liebe, neues leben, Op. 75, No. 2 (New love, new life)